St. Vincent and the Grenadines : Request for Disbursement Under the Rapid Credit Facility-Press Release; Staff Report; and Statement by the Executive Director for St. Vincent and the Grenadines. (IMF Staff Country Reports; Country Report ;, 2020)
This paper highlights St. Vincent and The Grenadines' Request for Disbursement Under the Rapid Credit Facility (RCF). The coronavirus disease 2019 (COVID-19) pandemic poses a major challenge to St. Vincent and the Grenadines. The tourism sector, a key driver of economic growth in the country, has come to a complete halt with ripple effects across the economy. The authorities have responded to the pandemic by swiftly implementing containment measures and a fiscal package, which includes an increase in funding for the health sector, various public construction projects to generate jobs, financial support to agriculture and fishery sector, and programs to support displaced workers and the most vulnerable. The authorities are committed to meeting the regional debt target of 60 percent of gross domestic product by 2030. Once the crisis has abated, they plan to reprioritize capital spending, contain the growth of the wage bill, enhance taxpayer compliance, and rationalize exemptions from import duties and value added tax on imports. IMF emergency support under the RCF will help fill St. Vincent and the Grenadines' balance of payments needs. The IMF financing will also help catalyze additional donor support. The authorities are committed to ensuring transparency and good governance in the use of COVID-19-related spending.